From collapse to constitution: The case of Iceland - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2012)
Most of the time, crises precede constitutions. Following a brief review of relevant historical background, this article aims to show why Iceland, after its financial collapse in 2008, is now at last on the road to adopting a new constitution to replace the provisional constitution from 1944. The aim is also to show how the constitutional bill of 2011 came into being with significant help from the general public. Further, the article outlines some of the key provisions of the bill as well as why and how it differs from the current constitution. The article concludes by offering a brief discussion of some potential obstacles to the adoption of the bill in parliament, the role of the public, and some lessons from, and for, other countries.
Keywords: K10; 330; Verfassungsreform; Finanzmarktkrise; Wirtschaftskrise; Island